SURGICAL ATTITUDES AND PREFERENCES REGARDING CHOICE OF ANAESTHESIA AMONGST ORTHOPAEDIC SURGEONS - Malik, Sara Haider; Saleem, Huma; Ashfaq, Allah Ditta; Malik, Nimra Haider; Abbasi, Tariq (Journal of Ayub Medical College Abbottabad, 2020)
Background: Regional anaesthesia is choice of anaesthesia for orthopaedic surgery due to lower side effects such as nausea, vomiting, postoperative pain and early mobilization. Despite of this, some orthopaedic patients refuse this modality. This study was conducted to interrogate the surgeons about their choice of anaesthesia in order to gain some insights into the concerns of surgeons and to change their minds and choose a safer mode of anaesthesia. The aim of the study was to assess the surgeons’ fears and their perception about regional anaesthesia. Methods: After institutional approval, thirty surgeons from three different tertiary care hospitals were interviewed. They were asked questions as per the questionnaire to choose choice of anaesthesia for their patients. Results: After regional anaesthesia, 27.6% of respondents were concerned about paralysis and neurological disorders, 34.5% about seeing and hearing whatever is happening in theatre, 17.2% about perioperative pain, 24.1% about backache and 24.1% about delayed discharge. The most important reason to change their mind was the reassurance that the complications are not as frequently as they thought their patient would receive after a block. Conclusion: Due to the lack of information on regional anaesthesia and the risks of general anaesthesia, orthopaedic surgeons’ fears and conceptions about regional anaesthesia are distorted. Anaesthesiologists should be aware of the concerns of the surgeons as well as the patients and should be willing to discuss the concerns with them and suggest the safest way to receive anaesthesia with evidence-based data. Keywords: Regional anaesthesia; general anaesthesia; post-operative complications